Seasonal variation in microbial contamination of Pleurotus ostreatus spawn - and ROBIN GOGOI*, N. MAZUMDER, Y. RATHAIAH (Indian Phytopathology, 2005)
Eight fungal and one bacterial contaminants from naturally contaminated spawn of oyster mushroom were isolated and identified. These were Aspergillus ffavus var. cotumneris, A. niger, Alternaria alternata, Penicillium janthinellum, Penicillium spp., Rhizopus stotoniter, Trichoderma harzianum, T. viride and Bacillus brevis. Month-wise variation in spawn contaminations caused by various fungal and bacterial contaminants was observed. The contamination was the highest during the monsoon season (28.57%) followed by pre-monsoon (21.90%). Type of substrates was found to have influence on spawn contamination. Paddy grain based spawn recorded significantly lowest (15.00%) contamination as compared to wheat grain based (30.00%) spawn.